CRITERIA OF QUALITATIVE CONDITION AND SINGULARITY OF STRESSES FOR CRACKS IN THREE-DIMENSIONAL BODIES - Матченко, Т. І. (Proceedings of National Aviation University (archive), 2021)
It is established that there are ten energy criteria for changing the nature of destruction; nine types of stress-strain state in the vicinity of the crack front area depending on the crack geometry. The expressions of invariant O-integrations for the generalized form of crack loading are given, which determine the change of the deformation energy with increasing length and crack front, crack area or its volume. For nine types of stress-strain state near the crack tip, the basic exponents at r for the displacement function are obtained.